2012
DOI: 10.1136/sextrans-2011-050170
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for primary care clinicians in providing shared care in HIV treatment? A systematic literature review

Abstract: Primary care has an important role in the shared care of the diagnosis and management of people with HIV. Some improvements with current guidelines on the management in primary care of people with HIV in developing countries should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…This finding is consistent with a small quantitative literature on HIV and primary care integration [64, 65] and found effective in high income settings [66, 67]. Several themes supported this finding (cessation support services for substance users, active referrals, and case management team counseling), highlighting the many ways in which integration could be effectively implemented [14, 17, 3336, 39, 40, 43, 4446, 48, 52].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with a small quantitative literature on HIV and primary care integration [64, 65] and found effective in high income settings [66, 67]. Several themes supported this finding (cessation support services for substance users, active referrals, and case management team counseling), highlighting the many ways in which integration could be effectively implemented [14, 17, 3336, 39, 40, 43, 4446, 48, 52].…”
Section: Discussionsupporting
confidence: 92%
“…Given that task shifting has not been widely implemented in locations with poor linkage to care [60, 61, 66], implementation research on how best to facilitate task shifting is needed, especially in settings with poor linkage to care. Second, research on linkage to care among women, adolescents, and children should be a priority given their under-representation in linkage to care research [3, 5, 63, 6567]. Third, as task shifting expands HIV service delivery into a wider range of settings, research on maintaining confidentiality and privacy will be important.…”
Section: Discussionmentioning
confidence: 99%
“…Although national guidance recommends involvement of primary care in the management of people with HIV, 13,27 there is no accepted scope or model for its delivery. For the purposes of this review, we used a broad definition of shared care 15,16 and applied it to the HIV setting.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that generalists provide equivalent care with regards to HIV outcomes[49, 50]; however, our sample did not classify providers by levels of experience, previously shown to impact HIV outcomes[26, 4446]. Our sample size for generalists is less than 6% of the overall sample, however, and reflects clinical practice patterns of many fewer providers compared with the ID and ID plus generalist groups.…”
Section: Discussionmentioning
confidence: 96%
“…Increased experience caring for PLWHA or HIV patient volume has been shown to affect the rate of incorporating new literature into practice[4246], HIV outcomes[47, 48], and mortality[49, 50]. Yet relatively few studies have assessed the optimal HIV care model—whether comprised of ID, generalist, or both—in terms of NCD screening in the current era of HIV care[2426], when prevention and management of chronic disease complications are key clinical priorities.…”
Section: Discussionmentioning
confidence: 99%